Unlocking a child's potential nurturing brilliance and shaping futures - Muhlfeit, Jan; Krêutovâa, Kateérina (Hoboken, NJ Wiley, 2024)
"Every child is a genius, let's discover their hidden talents. Unfortunately, the classic school system often does not develop strengths, but instead focuses on weaknesses and the elimination of mistakes. However, these four basic mistakes are committed by many parents and their children. Trying too hard to improve their weaknesses and forgetting about their strengths. Creating a plan of what to do rather than thinking about why they do it Trying to drive time instead of their energy. Focusing primarily on success instead of experiencing happiness Our book Unlocking Your Child's Potential helps parents and teachers to avoid these pitfalls and serves as a guide for parents who want something more for themselves and their children"--
Includes index.
Keywords: Child development; Child psychology; Parent and child